Inosperma pakistanicum sp. nov. (Inocybaceae, Agaricales) from Swat, Pakistan - Sana; Kiran, Munazza; Ali, Wajid (Phytotaxa, 2025)
Inosperma pakistanicum is described as a new species from the Swat District, Khyber Pakhtunkhwa, Pakistan. Morphological data and molecular phylogenetic analyses based on nrITS and nLSU sequences supported the fact that the species is a unique new species. Inosperma pakistanicum is characterized by campanulate to subumbonate and orange to bright brown pileus, subventricose and vivid purple to vivid reddish orange lamellae, abruptly bulbous and white to dark reddish brown stipe, broadly ellipsoid to elongate, smooth basidiospores (on average 9.79 × 6.60 μm), clavate basidia, narrowly utriform, few with median constriction cheilocystidia, oblong pileocystidia and absence of pleurocystidia and caulocystidia. The new species’ description, illustrations, phylogenetic analysis results, and comparison with closely related taxa are provided. A key to the Pakistan Inosperma species is also provided.